Effect of Fill Volume on Microclimate and Microbial Activity in Non-ventilated Clay Silos Storing Maize in the Humid Tropics (2019)
Silos have a fixed volume at the time of construction; harvests however vary from season to season. Complaints about severe postharvest losses in grains in the humid tropics of southern Nigeria necessitated a study into the effect of fill volume on quality of stored maize. Three clay silos labelled S1 to S3 of the same dimension and capacity (3.5 metric tonnes) were used. The silo walls were painted externally with gloss paint to reduce water absorption and filled with shelled maize. The first silo (S1) was filled with 3 tonnes, the second silo (S2) with 2 tonnes and the third (S3) filled with a tonne of maize for 6 months. Data was collected on microclimatic conditions within the silo and grain quality with increasing time of storage. Temperature, relative humidity (RH) and equilibrium moisture content (EMC) were recorded three times daily for each silo, focusing on the air between the grains and the headspace above the grains. Temperature fluctuations within S1 were smaller as indicated by the statistical range of 2 oC compared to S2 and S3 at 7 and 8 oC respectively. S3 showed high values of RH toward the end of storage, ranging between 65% to 80% at the top level and 76% at the bottom. EMC at the airspace above the grains in S1 increased from 12.0% at the beginning of storage in the dry season to 15.6% at the end of storage in the rainy season compared with S2 and S3 which increased from 12.0 to 17% and 12.0 to 17.2% respectively. Grains were found to be more prone to deterioration with decreasing level of fill because and increase in microbial activity was observed with a decreasing level of fill. Recommendations were made to farmers and grain aggregators on proper actions to take during grain storage given the peculiarities of the humid tropics.